2022
DOI: 10.1038/s41467-022-29490-3
|View full text |Cite
|
Sign up to set email alerts
|

In vivo base editing rescues cone photoreceptors in a mouse model of early-onset inherited retinal degeneration

Abstract: Leber congenital amaurosis (LCA) is the most common cause of inherited retinal degeneration in children. LCA patients with RPE65 mutations show accelerated cone photoreceptor dysfunction and death, resulting in early visual impairment. It is therefore crucial to develop a robust therapy that not only compensates for lost RPE65 function but also protects photoreceptors from further degeneration. Here, we show that in vivo correction of an Rpe65 mutation by adenine base editor (ABE) prolongs the survival of cone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…We believe that the bystander effect problem will be solved in the future. In this study, as in the previously reported a Rpe65-rd12 base editing study( 18 ), the positive effects of high levels of editing at the target site were much higher than the possible negative effects of the bystander despite the bystander editing.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We believe that the bystander effect problem will be solved in the future. In this study, as in the previously reported a Rpe65-rd12 base editing study( 18 ), the positive effects of high levels of editing at the target site were much higher than the possible negative effects of the bystander despite the bystander editing.…”
Section: Discussionsupporting
confidence: 76%
“…The adenine base editors (ABEs), which is composed of dCas9 and adenine deaminase, can convert A•T to G•C or C•G to T•A. In recent years, studies have reported that lentiviral vector-delivered ABE could correct Rpe65 mutation in the retinal pigment epithelium of rd12 mice, a mouse model of Leber congenital amaurosis (LCA)( 17, 18 ). To explore whether base editing can effectively rescue the dysfunction of photoreceptors and provide a potential therapeutic strategy for RP, we aimed to correct the Pde6b mutation in the rd10 mouse model, which recapitulates the human condition and is analogous to the mutations that cause human RP( 19, 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by testing contrast. Single units were recorded along the whole depth of the primary visual cortex (V1) as presented in previous studies ( Foik et al, 2018 ; Suh et al, 2020 ; Frankowski et al, 2021 ; Choi et al, 2022 ; Lewandowski et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The adenine and cytosine base editors were delivered and transduced efficiently into the retinal cells. However, small insertion and deletions were observed in the mice [ 89 ]. The prime editing has successfully edited the Dnmt1 gene in mouse retina with fewer off-target effects.…”
Section: Base and Prime Editing: Advanced Gene Editing Tools To Cure ...mentioning
confidence: 99%